Examining the Economic Costs of the 2003 Halloween Storm Effects on the North Hemisphere Aviation Using Flight Data in 2019 - Dabin Xue; Jian Yang; Zhizhao Liu; Shiwei Yu (Space Weather)
Abstract Space weather can impede normal aviation operations through communication blackouts, GNSS‐based navigation and surveillance failures, and elevated cosmic radiation, consequently resulting in necessary flight plan adjustments and considerable economic costs. Although space weather effects have been heavily emphasized, the literature on the economic effects on aviation is limited. In this study, we estimate the economic impacts from the perspective of air traffic management, assuming an extremely strong space weather event like the 2003 Halloween solar storm would occur in 2019 with a booming air transport industry in recent years. We find that (a) as the high‐frequency communication blackouts may lead to polar flight rerouting and cancellations, possible daily economic costs could range from €0.21 million to €2.20 million per day; (b) during the satellite navigation failure period in the continental United States, as aircraft utilizes ground navigation aids as a backup, the increased flying time and disrupted descent approach operations may lead to additional cost of €2.43 million; (c) a surveillance failure can reduce airspace capacity and increase the workload of air traffic controllers, resulting in fatigue and perhaps risking flight safety; (d) to prevent massive cosmic radiation exposure, the economic costs of flight cancellations can be from €2.77 million to €48.97 million, depending on the cosmic radiation dose limits for a given plan. Our study indicates that severe space weather events may briefly disrupt normal aviation operations and cause substantial economic losses if future aviation equipment and technology are fragile to its effects.